Prevalence of Helicobacter Pylori Infection among the Whole Spectrum of Age and the Performance of the Different Diagnostic Tests (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: helicobacter pylori; sensitivity; specificity; rapid urease test; gastric cancer; ELISA test; IgG to H pylori